2017
DOI: 10.1111/fwb.12959
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence in freshwater insects with contrasting dispersal capacity across a sea of desert

Abstract: Summary Arid landscapes pose arguably one of the greatest challenges to dispersal of aquatic insects, and may drive speciation in taxa with low dispersal potential. We investigated genetic divergence in aquatic insects with high and low dispersal potential between two regions within the Australian arid zone. We used two dragonfly species to infer patterns for strong‐dispersing species, and mayfly species from two genera to represent weak‐dispersing species. Based on dispersal‐related traits of the taxa, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…However, these fluvial characteristics have unequal influence on different organismal groups. For example, overland dispersal facilitates population connectivity of many aquatic insect groups (Geismar, Haase, Nowak, Sauer, & Pauls, ; Razeng et al, ), whereas such connectivity is improbable for fish and other species permanently bound to flowing rivers. Indeed, much of our understanding of gene flow and population genetic patterns in fluvial systems comes from studies of fish and aquatic insects (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these fluvial characteristics have unequal influence on different organismal groups. For example, overland dispersal facilitates population connectivity of many aquatic insect groups (Geismar, Haase, Nowak, Sauer, & Pauls, ; Razeng et al, ), whereas such connectivity is improbable for fish and other species permanently bound to flowing rivers. Indeed, much of our understanding of gene flow and population genetic patterns in fluvial systems comes from studies of fish and aquatic insects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fluker et al, 2014a;Fluker, Kuhajda, & Harris, 2014b;Fluker et al, 2010;Prunier, Dubut, Loot, Tudesque, & Blanchet, 2017;Thomaz, Malabarba, & Knowles, 2017;Van Leeuwen, Dalen, Museth, Junge, & Vøllestad, 2018) and insects (e.g. Finn & Adler, 2006;Finn et al, 2007;Geismar et al, 2015;Múrria et al, 2017;Razeng et al, 2017). Of the few molecular studies that have employed population-level sampling of pleurocerids, none have revealed fine-scale landscape genetic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies on species of mayfly (with winged dispersal stage) and amphipods (dispersal via movement within streams) have revealed greater intrapopulation and overall genetic diversity for mayflies inhabiting streams and reservoirs relative to amphipods (Zickovich & Bohonak, 2007) and decreasing genetic diversity along upstream gradients for populations of an amphipod but not for those of a mayfly (Alp, Keller, Westram, & Robinson, 2012). Comparative analyses of dragonfly and mayfly species with relatively high and low dispersal potentials across groundwater-fed riverine pool systems in arid environments provided evidence for ongoing gene flow among dragonfly populations and substantial genetic divergence among mayfly populations (Razeng et al, 2017). Finally, populations of mussel species in smaller rivers were characterized by reduced genetic diversity relative to populations of other mussel species in larger rivers-a pattern linked with the relative movements of mussel larvae (glochidia) provided by smaller and larger fish species according to river size (Berg, Christian, & Guttman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…) commented that A. bancrofti, unlike A. pestilens, occurred in dryer western Queensland and he wondered how populations survived-either with a drought resistant stage such as is known for A. pestilens, or by reintroduction when conditions were suitable. The latter point is of general interest to biogeographers of Australian arid regions (Razeng, et al, 2017;Majer et al, 2018). Indeed, Simulium ornatipes Skuse is known from southwest of Alice Springs at the George Gill Range, Northern Territories (S24.2556° E131.5702°), one of the driest regions in Australia (Davis et al,1993).…”
Section: Introductionmentioning
confidence: 99%